The effect of orifice diameter to the acoustic signal at the hot tube of a Ranque-Hilsch Vortex Tube / Khairil Muhaimin Abd Rahman...[et al.] - Abd Rahman, Khairil Muhaimin; Wirachman, Wisnoe; Istihat, Yusman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The orifice diameter is one of the parameters that influences the device performance. This study aims to investigate the effect of orifice diameter on the acoustic characteristics produced at the hot side of a Ranque-Hilsch Vortex Tube (RHVT). The orifice diameters were 2 mm, 3 mm, 4 mm, 5 mm and 6 mm. The sound produced is captured by a microphone located outside of the hot tube. The sound signal produced from the tube is transformed into frequency representation using FFT algorithm. Results show that the orifice diameters affect the sound recorded. The frequencies produced by the hot tube remain the same at particular location except when the frequency produced by the orifice is overheard by the microphone. The frequencies obtained from the transformation are then filtered to most significant peaks which are named as frequency signature. Acoustic signatures are obtained from each change in diameter which relate to thermofluid performance of each configuration of the RHVT.